Dissolved organic matter in the northwestern Pacific marginal seas: Insight into the distribution of its optical properties - Han, Heejun; Kim, Hyung Bo; Kim, Jeonghyun; Kim, Guebuem; Hwang, Jeomshik; Nam, SungHyun (Frontiers in Marine Science, 2023)
Dissolved organic carbon (DOC) and the optical properties of dissolved organic matter (chromophoric- and fluorescent dissolved organic matter; CDOM and FDOM) were measured to determine the distributions and drivers of DOM in the northwestern Pacific marginal seas, including the East China Sea, the Yellow Sea, and the East/Japan Sea, in August 2020. In this study, the concentrations of DOC and CDOM/FDOM in surface water showed good correlations with salinity, indicating a predominant contribution from the Changjiang River. However, significantly high concentrations of DOC and FDOM were also observed in the central Yellow Sea region, which seems to be produced mainly from the continental shelf-water and enriched over the water residence time of the Yellow Sea, while the lowest concentrations of DOC and CDOM/FDOM were found in high-salinity waters near the southern sea of Korea. In addition, the East/Japan Sea showed relatively low DOC concentrations and high FDOM values. To distinguish the physical mixing and biogeochemical processes of DOM, we estimated the water mass fractions using an optimum multi-parameter analysis with hydrological and DOM parameters of the major water masses in this region. Our results showed that five primary external drivers of DOM distribution were intrusions of (1) the Changjiang diluted water and (2) the Kuroshio Current water in the surface water, the mixing of (3) the Yellow Sea bottom cold water and (4) the Kuroshio sub-surface water in the bottom layer, and (5) upwelling of the East/Japan Sea water. We conclude that the distribution of DOM is significantly influenced by the mixing of multiple water masses, and the optical signature of DOM can be an effective proxy for tracing the origins and characteristics of DOM in this region.